Community based participatory epizootiology of livestock kept by Awotan Women, Ido LGA, Oyo State, Nigeria (2007)
Participatory Epizootiology (PE) is the use of participatory approaches and methods, involving the community based livestock keepers, to improve the understanding of their animal diseases and production problems, and to design appropriate veterinary intervention and other action plans for these problems Women are generally responsible for small stocks of livestock species kept in local communities This study was to investigate by the use of semi structured interviews, livestock diseases and health problems of traditional animal health projects in the study area, Awotan in Ido Local Government Area of Oyo State; with livestock keeping women as the primary respondents. The major species of animal kept were sheep and goats (51%), domestic fowl (27%), and dog (4%). They were kept under a semi intensive system of management in which the farmer have no adequate control over the animals. Common livestock diseases and health problems is encountered by female livestocks at Awotan were ranked by respondents as follows, Diarrhea (26%), Newcastle disease (22.7%), Mange (18%), Fowl pox 8.4%) petos des petite ruminants PPR (7.8%), Lice infestation 5.8%, Foot and nose bots 5.2%, Tick infestation 3.0%and Contagious Caprine Pleuro-pneumonia CCPP (1.95%). The farmers regard traditional intervention on the disease of their animals as very effective as a palliative treatment and modern veterinarian services as curative but less accessible and very expensive. Veterinary staff associated with the community complained about non conducive working environment and lack of mobility ambulatory vehicle, problems of ‘quacks’ that have motor cycles and go around disguising as veterinary doctors. Recommendations are made for the training of some educated community members as community animal health workers, the control of quackery in the Awoton, the provision of adequate mobility and conducive working environment for Veterinary staff, as well as provision of veterinary services to farmers at affordable prices.